2019
DOI: 10.1007/s10732-018-9403-z
|View full text |Cite
|
Sign up to set email alerts
|

Clustering-driven evolutionary algorithms: an application of path relinking to the quadratic unconstrained binary optimization problem

Abstract: A long-standing challenge in the metaheuristic literature is to devise a way to select parent solutions in evolutionary population-based algorithms to yield better offspring, and thus provide improved solutions to populate successive generations. We identify a way to achieve this goal that simultaneously improves the efficiency of the evolutionary process. Our strategy derives from a proposal associated with the scatter search and path relinking evolutionary algorithms that prescribes clustering the solutions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Pudenz and Lidar (2013) An application of QUBO to unsupervised machine learning in provides an approach that can be employed either together with quantum computing or independently. In a complementary development, clustering is used to facilitate the solution of QUBO models in Samorani et al (2018), thereby providing a foundation for studying additional uses of clustering in this context.…”
Section: Y = 2588mentioning
confidence: 99%
“…Pudenz and Lidar (2013) An application of QUBO to unsupervised machine learning in provides an approach that can be employed either together with quantum computing or independently. In a complementary development, clustering is used to facilitate the solution of QUBO models in Samorani et al (2018), thereby providing a foundation for studying additional uses of clustering in this context.…”
Section: Y = 2588mentioning
confidence: 99%
“…There remains a possibility that earlier stopping points will still yield overall results that are as good, where solutions gradually improve to a desired level even if they are not as good at some intermediate point. It may additionally be observed that X * may be constructed by reference to clustering, using clustering ideas as proposed by Glover and Laguna [16] and Samorani et al [17]. For constructing X * , the focal distance algorithm can keep track of the best solutions x * (including in a variant that initially applies the single solution x * approach) and then using clustering to group solutions that are closer together to form new X * sets.…”
Section: Main Routinementioning
confidence: 99%
“…Algorithms 5, 9 and 11 can be used to address this issue, embedded in MOO approaches, similarly to [49]. Archiving diversified solutions of Pareto sets has application for the diversification of genetic algorithms, to select diversified solutions for cross-over and mutation phases [61,62], but also for swarm particle optimization heuristics [63]. In these applications, clustering has to run quickly.…”
Section: Applications To Bi-objective Meta-heuristicsmentioning
confidence: 99%